Availability and cost of online search services. - SAFFADY, William (1996)
Describes the type of databases offered by online search services available to North American libraries and discusses their competitive positions. Examines the costs associated with library-based online searching. Reviews the most important fixed and variable cost components, emphasizing differences among available online search services as well as recent trends in search service pricing. Considers the competitive relationship of online search services and local implementation of specific data bases.